2003
DOI: 10.1051/rnd:2003005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coconut oil and defaunation treatment on methanogenesis in sheep

Abstract: -The present study was conducted to evaluate in vivo the role of rumen ciliate protozoa with respect to the methane-suppressing effect of coconut oil. Three sheep were subjected to a 2 × 2 factorial design comprising two types of dietary lipids (50 g·kg -1 coconut oil vs. 50 g·kg -1 rumenprotected fat) and defaunation treatment (with vs. without). Due to the defaunation treatment, which reduced the rumen ciliate protozoa population by 94% on average, total tract fibre degradation was reduced but not the methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
77
4
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 46 publications
(62 reference statements)
12
77
4
2
Order By: Relevance
“…There is not a clear relationship between the number of methanogens and methanogenesis in the rumen (Nollet et al, 1998;Machmü ller et al, 2003a and2003b;Yanez-Ruiz et al, 2008;Mosoni et al personal communication), except for trials when specific inhibitors of methanogenesis were used (i.e. BSM; Denman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There is not a clear relationship between the number of methanogens and methanogenesis in the rumen (Nollet et al, 1998;Machmü ller et al, 2003a and2003b;Yanez-Ruiz et al, 2008;Mosoni et al personal communication), except for trials when specific inhibitors of methanogenesis were used (i.e. BSM; Denman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the use of specific forage species, forage conservation methods and dietary lipid supplements can be used to alter milk fat composition in ruminants (Dewhurst et al, 2006;Chilliard et al, 2007;Glasser et al, 2008a). Furthermore, plant oils and oilseeds in the diet also decrease methanogenesis in ruminants (Machmü ller et al, 2003;Martin et al, 2008;Beauchemin et al, 2009). Due to the interrelationship between diet composition, rumen metabolism and mammary lipogenesis, on-farm feeding regimens for decreasing greenhouse gas emissions or altering milk fatty acid composition can also be expected to influence milk fat content ) depending on diet composition and ruminant species.…”
Section: Introductionmentioning
confidence: 99%
“…Workers 9 have suggested that reduction in methane emission by up to 80% in vitro and about 25% in vivo might be possible with an addition of oils to the diets. .…”
mentioning
confidence: 99%